A Novel Study of Graphs Based on m-Polar Cubic Structures. (22nd April 2022) - Muhiuddin, G.; Alanazi, A. M.; Mahboob, A.; Alkhaldi, A. H.; Alatwai, Wejdan
Abstract : By combining the notions of interval-valued m-polar fuzzy graphs and m-polar fuzzy graphs, the notion of m-polar cubic graphs is first introduced. Then, the degree of a vertex in m-polar cubic graphs and complete m-polar cubic graphs is defined. After that, the concepts of direct product and strong product of m-polar cubic graphs are given. Moreover, weak isomorphism and co-weak isomorphism are defined, and examples are given to prove that weak isomorphism and co-weak isomorphism are not an isomorphism. Finally, the notion of complement m-polar cubic graphs and weak complement m-polar cubic graphs is presented.